Patient Experience and Satisfaction of Orthodontic Retention after Treatment in Saudi Arabia - Aldosari, Mohammad; Alrahmah, Waad; Al Hammad, Fadila; Alhmadi, Rahaf; Ansari, Shahzeb; Alzahrani, Khames (International Journal of Innovative Research in Medical Science, 2021)
Background: Orthodontics treatment aimed to make patient satisfied about treatment result starting from appearance to the function. Orthodontic retention is consider as important stage to stabilize the result of orthodontic treatment and avoid relapse that caused by normal age changes. Methods: A cross-sectional study performed through patient questionnaires. A total of 450 patients were included in the study. The questionnaire included 19 questions. The questionnaire consisted of question about socio-demographic status of the respondents such as age, gender, also included question about the type of retainer fixed or removable retainers that were used, duration of wearing retainer and Retention protocol. Result: In our study majority of the participants were females (87.3%), and 55.3% belonged to the 20-25 years age group. The fixed orthodontic related history showed 59.8% had undergone the treatment for 1 to 3 years and 31.6% of the participants reported that they had removed the fixed braces for more than five years. Among these participants, 89.5% (n=34) reported that the fascia (space) closed between the upper frontal teeth after Frenectomy, and 65.8% (n=25) agreed that spaced between the two upper front teeth still closed after removing the retainer. Conclusion: The study findings showed that the majority of the participants were aware of the frequency and duration of wearing retainers but didn't completely adhere to the instructions given by the orthodontists and/or dentists. The major reason for not using retainers was difficulty in speaking or uncomfortableness.